Towards a consistent model of the hot quadruple system HD 93206=QZ Carin ae II. N-body model - Broz, M.; Harmanec, P.; Zasche, P.; Catalan-Hurtado, R.; Barlow, B. N.; Frondorf, W.; Wolf, M.; Drechsel, Horst; Chini, R.; Nasseri, A.; Labadie-Bartz, J.; Christie, G. W.; et al. (Astronomy & Astrophysics, 2022)
Aims. HD 93206 is a massive early-type stellar system composed of components resolved by direct imaging (Ab, Ad, B, C, D) and a compact subsystem (Aa1, Aa2, Ac1, Ac2). Its geometry was already determined on the basis of extensive photometric, spectroscopic, and interferometric observations. However, the fundamental absolute parameters are still not known precisely enough.
CRIS-Team WoS Importer:2022-11-04